If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(9x + -1) = 6(x + 15) Reorder the terms: 5(-1 + 9x) = 6(x + 15) (-1 * 5 + 9x * 5) = 6(x + 15) (-5 + 45x) = 6(x + 15) Reorder the terms: -5 + 45x = 6(15 + x) -5 + 45x = (15 * 6 + x * 6) -5 + 45x = (90 + 6x) Solving -5 + 45x = 90 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 45x + -6x = 90 + 6x + -6x Combine like terms: 45x + -6x = 39x -5 + 39x = 90 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + 39x = 90 + 0 -5 + 39x = 90 Add '5' to each side of the equation. -5 + 5 + 39x = 90 + 5 Combine like terms: -5 + 5 = 0 0 + 39x = 90 + 5 39x = 90 + 5 Combine like terms: 90 + 5 = 95 39x = 95 Divide each side by '39'. x = 2.435897436 Simplifying x = 2.435897436
| 5(9x-1)=6x(x+15) | | 5x+83=11x+11 | | -6x-23(x+6)=-7(4x+9) | | y^3-7y^2+10y= | | s^2+11s+30= | | (-2+2y)y+3(-2+2y)=10 | | 6t(11t+5)= | | 4(3k-1)=11 | | 5x-22=18 | | 9c^3-1c= | | 2y=-2-x | | 5x^2-26x+5= | | 7p-8q=44 | | 4(3t-1)=20 | | 12x+6(9-x)=3x-21 | | 2x^2-15x+18= | | 3(t+2)=9 | | 12a^2-51a-45= | | 2(3y-2)=5 | | 2(3x+4)=26 | | 3(3x+4)=26 | | (16-y)*y=63 | | 16y=y^2 | | F=7(s-55)+90 | | 15h^2+20h-30= | | 3(5y-5)-10=6(2y-1)+11 | | 2(5y-5)-23=4(4y+5)+1 | | 2(4x-3)=6(2x+3) | | 6(2x-2)=3(5x-5) | | 6(5x-1)=-9x+6 | | 7(3y-3)=14 | | 6(3y+1)=-32 |